PENGARUH MOTIVASI INSTRINSIK DAN MOTIVASI EKSTRINSIK TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN ILMU PENGETAHUAN SOSIAL - Afianti, Renni; Herkulana, Herkulana; Syahrudin, Husni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research uses quantitative research methods and is carried out at Silat Hilir State 3 Middle School in Kapuas Hulu Regency, with a sample of 119 students. Data collection was carried out using a questionnaire and documentary and analyzed using the SPSS program version 22.1.(1) Intrinsic motivation possessed by students on social studies subjects in relation to their learning outcomes is quite good; (2) Extrinsic motivation possessed by students in social studies subjects in improving their learning outcomes is quite good; (3) The learning outcomes achieved by students in social studies include good enough categories; (4) There is a partially positive effect on intrinsic motivation on learning outcomes achieved by students in social studies subjects; (5) There is a partially positive effect on extrinsic motivation on student learning outcomes in social studies subjects; (6) There is a simultaneous positive effect on intrinsic motivation and extrinsic motivation on student learning outcomes in social studies subjects.From the results of this study it is suggested: (1) In an effort to increase students' intrinsic motivation in participating in social studies lessons, it is necessary to assign tasks that are factual; (2) In an effort to increase the intrinsic motivation possessed by students in attending social studies lessons, it is necessary to be given more encouragement by teachers by giving gifts and penalties. (3) For social studies teachers, it is necessary to further enhance their professional abilities in teaching.Â Keyword : Motivation, intrinsic, extrinsic, learning outcomes.